"Beautiful solutions": The business case for city resilience. Issue 3 (3rd July 2019) - Smith, David
Abstract : Cities around the world are grappling with how to improve their resilience in the face of extreme weather events. The cheapest approach may be to turn cities into bunkers able to withstand the worst storm surge, but a new report from engineering consultancy Arcadis argues this can be counter-productive as it degrades the intrinsic value of a place, hurting investment and tourism. More sophisticated, "beautiful" solutions cost more, which is why the private sector should be drafted in to share the burden.